Cost-effectiveness of two screening strategies based on Chinese diabetes risk score for pre-diabetes in China - Hao, Jingjing; Yao, Qiang; Lin, Yidie; Sun, Yue; Zhang, Baiyang; Hu, Meijing; Zhang, Jing; Zhao, Ningxuan; Pei, Jiao; Liu, Zhonghua; Zhu, Cairong (Frontiers in Public Health, 2022)
Objective: Studies have shown that screening for pre-diabetes mellitus(pre-DM) is essential to prevent type 2 diabetes mellitus (T2DM). This study evaluates the cost-effectiveness of two screening strategies that apply the Chinese Diabetes Risk Score (CDRS) to screen for pre-DM in China. Methods: A Markov microsimulation model was conducted from a social perspective, and the input parameters were obtained from published literature or publicly available data. Two screening strategies for pre-DM based on CDRS were built and compared with the control group to determine the cost-effective strategy. The screening strategy of the control group was screening for pre-DM by fasting plasma glucose (FPG) test in adults undergoing annual health examination and no screening in adults without an annual health examination (status quo). Two screening strategies were strategy 1: screening for pre-DM using CDRS in all adults (including with or without an annual health examination); and strategy 2: supplemental self-screening for pre-DM using CDRS in adults without an annual health examination, based on the status quo. We focus on the cumulative prevalence of T2DM and the incremental cost-effectiveness ratio which signifies the cost per case of T2DM prevented. We also evaluated the cost-effectiveness from the health system perspective. One-way and probabilistic sensitivity analyses were conducted to verify the robustness of the results. Results: The costs a case of T2DM prevented for strategy 1 compared with the control group and strategy 2 were 299.67(95% CI 298.88,300.46) and 385.89(95% CI 381.58,390.20), respectively. In addition, compared with the control group, the cost of strategy 2 to prevent a case of T2DM was 272.23(95% CI 271.50,272.96). Conclusions: Screening for pre-DM using CDRS in all adults was the most cost-effective health policy. We suggest that medical institutions replace FPG with CDRS for pre-DM screening; at the same time, self-screening for pre-DM using CDRS is widely promoted among adults without an annual health examination. There were still some disputes about how CDRS is included in the health examination projects, so strategy 2 should be considered as an alternative screening strategy. Findings provide a reference for the application of the CDRS in pre-DM screening and contribute to T2DM prevention.